English Teachers’ Readiness in Implementation of ‘Merdeka Belajar’ Curriculum in Teaching English at Junior High School in Padang - Sania Tricahyati; M. Zaim (Universitas Negeri Padang, 2023)
This research aimed to investigate English teachers' readiness and the obstacles that faced in implementation of Merdeka Belajar curriculum. Thirteen junior high school English teachers from eight piloting schools (Sekolah Penggerak) in Padang were assigned to complete a questionnaire about their readiness and were interviewed the obstacles that faced in implementation of Merdeka Belajar curriculum. Quantitative analyses were employed in the research which using likert scale approach to measure the questionnaire and calculated in the average score, while data from interview were transcribed, classified and then draw conclusion. The results from quantitative analysis showed that teachers' readiness to implement the curriculum in level 3 or in category ready but need a little improvement with average score 3,20. The interview result showed that teachers have obstacle in formulating learning outcomes and applied differentiated learning in the process in teaching learning. Even the teachers is in category ready, they still need workshop and training which focused on assessment and utilization IT to help teacher create interactive media, so the teacher will be more prepare to implementation of Merdeka Belajar curriculum.